PENGARUH LIKUIDITAS (CURRENT RATIO) TERHADAP RETURN SAHAM: PERAN PEMEDIASI PROFITABILITAS (RETURN ON EQUITY) PADA PERUSAHAAN SUB SEKTOR KONSTRUKSI BANGUNAN DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Hidayat, Taufik (Jurnal Fokus Manajemen Bisnis, 2020)
This study aims to determine the effect of the liquidity ratio (CR) on stock returns with the role of profitability (ROE) as a mediator. This study takes the object of building construction sub-sector companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The population in this research is all companies in the building construction sub sector listed on the Indonesia Stock Exchange in the 2016-2018 period as many as 17 companies. The sampling technique uses purposive sampling using several criteria, namely the building construction sub-sector companies listed on the Indonesia Stock Exchange in the 2016-2018 period, companies that submit financial reports during the research period and companies that have positive net income reports. The number of samples that fit the criteria were 10 companies. The data analysis tool uses panel data regression analysis using Eviews 6. The results of the study show that the current ratio has a negative effect on stock returns, the current ratio has a positive effect on return on equity, return on equity has a negative effect on stock returns.